2021
DOI: 10.3389/fnut.2021.640538
|View full text |Cite
|
Sign up to set email alerts
|

Can a Higher Protein/Low Glycemic Index vs. a Conventional Diet Attenuate Changes in Appetite and Gut Hormones Following Weight Loss? A 3-Year PREVIEW Sub-study

Abstract: Background: Previous research showed that weight-reducing diets increase appetite sensations and/or circulating ghrelin concentrations for up to 36 months, with transient or enduring perturbations in circulating concentrations of the satiety hormone peptide YY.Objective: This study assessed whether a diet that is higher in protein and low in glycemic index (GI) may attenuate these changes.Methods: 136 adults with pre-diabetes and a body mass index of ≥25 kg/m2 underwent a 2-month weight-reducing total meal rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The mixed results may be partly attributed to the differences between studies, which includes the number of participants and methods of appetite assessment. In a PREVIEW sub-study (n = 136) conducted in Sydney, Australia, Buso et al (43) found no difference in fasting hunger ratings between the MP-moderate GI vs. the HPlow GI groups during 3-years WLM. In that study, appetite sensations were assessed in the fasting condition, whereas in the present study, overall sensations in the previous week were recorded.…”
Section: Discussionmentioning
confidence: 98%
“…The mixed results may be partly attributed to the differences between studies, which includes the number of participants and methods of appetite assessment. In a PREVIEW sub-study (n = 136) conducted in Sydney, Australia, Buso et al (43) found no difference in fasting hunger ratings between the MP-moderate GI vs. the HPlow GI groups during 3-years WLM. In that study, appetite sensations were assessed in the fasting condition, whereas in the present study, overall sensations in the previous week were recorded.…”
Section: Discussionmentioning
confidence: 98%